UPAYA DINAS PASAR, KEBERSIHAN DAN PERTAMANAN DALAM MENINGKATKAN RETRIBUSI PASAR DAYUN DI KABUPATEN SIAK TAHUN 2010-2013 - Anggoro, Prihadi Trisno; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The application of Otonomi Daerah (local autonomy) is focusing on area of Kabupaten and Kota. The local government of Kabupaten Siak develops funding mechanism by exploring several kinds of funding format that is potential to support local development and in the same time improve the quality of service, infrastructures for market, especially traditional market. Among all the retribution in Kabupaten Siak, sanitation (kebersihan) and garden affairs (perkebunan) is market services retribution based on Siak local rules (peraturan daerah kabupaten siak no 22 tahun 2011) about retribution of market services.Result shows that there are two kinds of effort in improving Dayun market retribution, which are norms (peraturan daerah kabupaten siak no 22 tahun 2011 about retribution of market services, SK of Bupati Siak, ) and empirical effort consist of space for trading rules, improving facilities, field inspection, and training. That's why writer entitled this reseach as " The effort of Dinas Pasar, Kebersihan and pertamanan in improving Dayun market retribution in kabupaten siak year 2010-2013"Key word: retribution, dayun market, local autonomy